Selenoprotein P Regulates Synaptic Zinc and Reduces Tau Phosphorylation - Kiyohara, Arlene C. P.; Torres, Daniel J.; Hagiwara, Ayaka; Pak, Jenna; Rueli, Rachel H. L. H.; Shuttleworth, C. William R.; Bellinger, Frederick P. (Frontiers in Nutrition, 2021)
Selenoprotein P (SELENOP1) is a selenium-rich antioxidant protein involved in extracellular transport of selenium (Se). SELENOP1 also has metal binding properties. The trace element Zinc (Zn2+) is a neuromodulator that can be released from synaptic terminals in the brain, primarily from a subset of glutamatergic terminals. Both Zn2+ and Se are necessary for normal brain function. Although these ions can bind together with high affinity, the biological significance of an interaction of SELENOP1 with Zn2+ has not been investigated. We examined changes in brain Zn2+ in SELENOP1 knockout (KO) animals. Timm-Danscher and N-(6-methoxy-8-quinolyl)-p-toluenesulphonamide (TSQ) staining revealed increased levels of intracellular Zn2+ in the SELENOP1-/- hippocampus compared to wildtype (WT) mice. Mass spectrometry analysis of frozen whole brain samples demonstrated that total Zn2+ was not increased in the SELENOP1-/- mice, suggesting only local changes in Zn2+ distribution. Unexpectedly, live Zn2+ imaging of hippocampal slices with a selective extracellular fluorescent Zn2+ indicator (FluoZin-3) showed that SELENOP1-/- mice have impaired Zn2+ release in response to KCl-induced neuron depolarization. The zinc/metal storage protein metallothionein 3 (MT-3) was increased in SELENOP1-/- hippocampus relative to wildtype, possibly in response to an elevated Zn2+ content. We found that depriving cultured cells of selenium resulted in increased intracellular Zn2+, as did inhibition of selenoprotein GPX4 but not GPX1, suggesting the increased Zn2+ in SELENOP1-/- mice is due to a downregulation of antioxidant selenoproteins and subsequent release of Zn2+ from intracellular stores. Surprisingly, we found increased tau phosphorylation in the hippocampus of SELENOP1-/- mice, possibly resulting from intracellular zinc changes. Our findings reveal important roles for SELENOP1 in the maintenance of synaptic Zn2+ physiology and preventing tau hyperphosphorylation.